Pengembangan Media Pembelajaran Matematika Articulate Storyline Terhadap Kemampuan Pemahaman Konsep Matematis Siswa di Kelas VIII-2 MTs Nurul Islam Indonesia Medan - Nilam Sari Simarmata; Nurhasanah Siregar (Lembaga Pengembangan Kinerja Dosen, 2023)
This research aims to determine the validity, practicality, effectiveness and how the students' answers process in completing the conceptual understanding ability test of the developed Articulate Storyline. This type of research is ADDIE model development research. The subjects of this research were 15 students in class VIII-2. The research results showed that the validity of the media was 85% before revision and 98% after revision from material experts and 61.67% before revision and 98% after revision from media experts on very valid criteria. The practicality of the media has met practical criteria, based on teacher responses obtained at 100% and from student responses obtained at 92.36%. The effectiveness of the media has met the effective criteria in terms of classical student learning completeness reaching 86.67%, use of research time in accordance with the RPP, and student response of 91.67%. The N-Gain test result is 0.70 in the high category. For the student answer process on the ability test (pre-test) it was 38.89%, increasing to 46.67% on the final ability test (post-test). Increasing students' ability to understand mathematical concepts strengthens the development of Articulate Storyline mathematics learning media in the classroom learning process.